Impact of Electronic Health Record Implementation on Ophthalmology Trainee Time Expenditures - Gali, Helena E.; Baxter, Sally L.; Lander, Lina; Huang, Abigail E.; Millen, Marlene; El-Kareh, Robert; Nudleman, Eric; Chao, Daniel L.; Robbins, Shira L.; Heichel, Christopher W.D.; Camp, Andrew S.; Korn, Bobby S.; Lee, Jeffrey E.; Kikkawa, Don O.; Longhurst, Christopher A.; Chiang, Michael F.; Hribar, Michelle R.; Ohno-Machado, Lucila (Journal of Academic Ophthalmology, 2019)
Objective Electronic health records (EHRs) are widely adopted, but the time demands of EHR use on ophthalmology trainees are not well understood. This study evaluated ophthalmology trainee time spent on clinical activities in an outpatient clinic undergoing EHR implementation.Design Prospective, manual time-motion observations of ophthalmology trainees in 2018.Participants Eleven ophthalmology residents and fellows observed during 156 patient encounters.Methods Prospective time-motion study of ophthalmology trainees 2 weeks before and 6 weeks after EHR implementation in an academic ophthalmology department. Manual time-motion observations were conducted for 11 ophthalmology trainees in 6 subspecialty clinics during 156 patient encounters. Time spent documenting, examining, and talking with patients were recorded. Factors influencing time requirements were evaluated using linear mixed effects models.Main Outcome Measures Total time spent by ophthalmology residents and fellows per patient, time spent on documentation, examination, and talking with patients.Results Seven ophthalmology residents and four ophthalmology fellows with mean (standard deviation) postgraduate year of 3.7 (1.2) were observed during 156 patient encounters. Using paper charts, mean total time spent on each patient was 11.6 (6.5) minutes, with 5.4 (3.5) minutes spent documenting (48%). After EHR implementation, mean total time spent on each patient was 11.8 (6.9) minutes, with 6.8 (4.7) minutes spent documenting (57%). Total time expenditure per patient did not significantly change after EHR implementation (+0.17 minutes, 95% confidence interval [CI] for difference in means: –2.78, 2.45; p = 0.90). Documentation time did not change significantly after EHR implementation in absolute terms (+1.42 minutes, 95% CI: –3.13, 0.29; p = 0.10), but was significantly greater as a proportion of total time (48% on paper to 57% on EHR; +9%, 95% CI: 2.17, 15.83; p = 0.011).Conclusion Total time spent per patient and absolute time spent on documentation was not significantly different whether ophthalmology trainees used paper charts or the recently implemented EHR. Percentage of total time spent on documentation increased significantly with early EHR use. Evaluating EHR impact on ophthalmology trainees may improve understanding of how trainees learn to use the EHR and may shed light on strategies to address trainee burnout.
Keywords: electronic health record; documentation time; talking time; examination time; time-motion; ophthalmology trainee; paper chart; burnout